Healthcare Information Systems, Second Edition - Beaver, Kevin (CRC Press, 2009)
The move to manage medicine from a financial perspective, i.e. managed care, has added huge layers of bureaucratic and administrative functions to healthcare. The need to have the ability to track patient medical records, mandated by government legislation such as HIPAA, is bringing new technologies and processes into the healthcare arena. A universal medical record system and absolute patient portability is a definite possibility in the not too distant future. All of these issues beg for clear IT solutions.